THE ROLE OF VILLAGE EQUIPMENT IN THE ACCOUNTABILITY OF CINTAMULYA VILLAGE GOVERNMENT SUMEDANG DISCTRICTWEST JAVA PROVINCE - Yaya Mulyana; Achdiat Achdiat (LPM Universitas Pasundan, 2021)
This study aims to determine how the role of village officials in Cintamluya Village, Jatinangor District in the accountability of village fund management. Data collection techniques used in this study were interviews and documentation. The subjects of this study amounted to 7 people who are village officials in Cintmulya Village, namely the Village Head, Village Secretary, Village Treasurer, Head of Development, Head of General Affairs, Head of Government and Head of Dusun. This study uses a descriptive method with a qualitative approach. The results of the research conducted indicate that village officials in Cintamulya Village have played a role in the accountability of village fund management by carrying out their duties starting from the planning, implementation, administration, reporting, accountability,